Initial clinical experience using fractal methods in complex systems analysis of diagnostic images - Bubnov, R. V.; Melnyk, I. M. (Видавництво Львівської політехніки, 2011)
The report describes the application of fractal analysis in complex systems of visual diagnostics in order to expand its diagnostic capabilities by increasing the information content for intelligent decision modeling to reduce subjectivity in the perception and interpretation.
Keywords: ultrasonography; mathematical modeling; imaging fractal analysis; fractal dimension